Comparison between the previous and current method of copex distribution and optimization of Robi Axiata Limited - Sarah Sarwar, Sarwat (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.